Directions of transformation of the stable gas condensate hydrocarbons on a zeolite catalyst under zeoforming conditions; Petroleum and Coal; Vol. 62, iss. 3 - Bogdanov I. A. Ilya Aleksandrovich; Altynov A. A. Andrey Andreevich; Kirgina M. V. Mariya Vladimirovna; Mardanov K. E. Kanan Elshad-ogly (2020, 2020)
Title screen